2006
DOI: 10.1111/j.1365-2893.2006.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and response to peginterferon plus ribavirin treatment of hepatitis C virus genotype 4 infection

Abstract: Hepatitis C virus genotype 4 (HCV-4) infection is progressing in Europe, where epidemiology and sustained virological response (SVR) seem to be different than in the Middle East. We analysed epidemiological features and SVR rates in a retrospective study of 1532 HCV-4-infected patients, including 1056 patients infected in France, 227 immigrants infected in Egypt and 249 in sub-Saharan Africa. SVR rates were assessed in 242 naive patients of the 1532, who received peginterferon plus ribavirin for 48 weeks. HCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
106
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 33 publications
20
106
2
3
Order By: Relevance
“…However, our data also show that the contribution of genotype 4 to the study pool is not exclusive and that other genetically related genotypes exist in the population, confirming previous studies (14,37,38). One cansuggest a deficiency of the multiplex PCR in subtyping genotype 4, but inclusion of more primers would be an unjustified burden on an already financially challenged health care system, in the absence of sufficient evidence to support clinical and therapeutic outcomes (23,24).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, our data also show that the contribution of genotype 4 to the study pool is not exclusive and that other genetically related genotypes exist in the population, confirming previous studies (14,37,38). One cansuggest a deficiency of the multiplex PCR in subtyping genotype 4, but inclusion of more primers would be an unjustified burden on an already financially challenged health care system, in the absence of sufficient evidence to support clinical and therapeutic outcomes (23,24).…”
Section: Discussionsupporting
confidence: 86%
“…To date, 18 subtypes have been identified (21,22). However, the full clinical significance of HCV-4 subtypes is not known, because few studies have been conducted on the correlation between HCV-4 subtypes and the natural history of the disease, pathogenicity, disease severity, and therapeutic outcomes (23,24). In this study, HCV chronic hepatitis was more frequent in males (14,(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 78%
“…The reported SVRs range between 59.7 and 67.8%. On the contrary, similar European studies report significantly lower SVRs, without being able to explain these observations by differences in patient baseline characteristics like age, naïve status or fibrosis stage [15][16][17]. In our study, genotype 4 HCV patients achieved SVR in 39.7%, similar to previously reported percentages in Greece [20,21].…”
Section: Discussionsupporting
confidence: 62%
“…Data on the efficacy of current combination therapy with pegylated interferon-α (Peg-IFNα) plus weight-based ribavirin is limited and contradictory; sustained virological response (SVR) rates of more than 60% reported in endemic areas [8][9][10][11][12][13][14] are approximately two times higher than those encountered in Europe [15][16][17]. In Greece, genotype 4 accounts for about 15% of all HCV infections [18][19][20][21][22] and is generally considered as "difficult to treat" in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also demonstrated that patients infected with HCV subtype 1b had a higher antiviral response than did patients infected with HCV subtype 1a (29). Another study of 1,532 patients infected with HCV genotype 4 showed that subtype 4a was more sensitive to anti-HCV treatment than was subtype 4d (36). Moreover, the development of new specific inhibitors of HCV enzymes whose antiviral responses and resistance profiles may be determined by the HCV subtype may require identification of the subtype prior to treatment (7,20,24).…”
Section: Discussionmentioning
confidence: 95%